Service quality delivery and consumers’ choice of fast-food outlets - Etuk, Aniebiet; Anyadighibe, Joseph A.; Amadi, Christian; James, Edim Eka (International research journal of management, IT and social sciences, 2022)
This study examined the effect of service quality delivery on consumer’s choice of fast foods outlets. Cross-sectional survey research design was adopted. Primary data was collected from respondents using structured questionnaire. Simple regression in the Statistical Package for Social Science (SPSS) was adopted to analyze the data collected. Consequently, it was found that service tangibility, reliability, responsiveness, assurance and empathy had significant effects on consumer’s choice of fast foods. Thus, it was recommended amongst others, that fast food outlets should be more responsive to consumers’ service requirements by rapidly eliciting and resolving consumers’ enquiries and complaints; consistently deliver fast, strong and reliable service; ensure their personnel treat consumers with politeness and consideration at every point of service encounter and constantly seek ways to offer freshness in order to remain relevant in the market place.